Inguinal Hysterocele And Its Surgical Management In A Bitch - Simon, M. Shiju; Kannan, T. A. (Indian Journal of Veterinary Sciences and Biotechnology, 2011)
Inguinal hernias are relatively common in dogs and most often involve old intact bitches (Parkes, 1981). It may be direct or indirect hernia in females and direct hernia in males. Most important cause of inguinal hernia in domestic animals is enlargement of the entrance of the vaginal process, which remains open (Hayes, 1974). Bitch may be predisposed as the inguinal canal is shorter and larger in diameter than in males (Elkins, 1983). Most inguinal hernias appear during estrus or in pregnant bitches (Water, 1993). Unilateral Inguinal hernia occur more on left side than on right side (Dorn, 1981). Contents of the inguinal hernia may include omentum, fat, ovary, uterus, small intestine, colon, bladder and spleen (Alvarenga, 1991). This paper discusses the surgical management of inguinal hysterocele in a bitch.